The Concept of a Joint Arab Force of the League of Arab States From 2015 as a Tool to Fight against Terrorism - Pogońska-Pol, Magdalena (Tools of War, 2023)
In 2015, thanks to Egypt, the League of Arab States returned to the idea of establishing joint Arab forces. The idea is not a new concept, it first appeared in the 1950s. Under the Treaty on Common Defense and Economic Cooperation, the Joint Defense Council was established as a body responsible for coordinating the military effort of the Arabs. The AL then tried to respond to external conflicts and resolve intra-Arab disputes using peaceful means of resolving them, with a view to respecting the countries territorial integrity and Arab unity. The threats that appeared in the region after the Cold War, including terrorism, and the effects of the social protests known as the Arab Spring on the Middle East – the development of terrorist organizations, civil wars – led to the resumption of talks on military cooperation in the fight against the challenges. At the 26th Arab Summit in Sharm el-Sheikh in March 2015, it was proposed to create a joint Arab force as a rapid reaction force. For this purpose, the organizational structure was reformed and the competences of the Arab Peace and Security Council were expanded. Then, a draft agreement was developed specifying the goals, tasks, method of operation and financing of these forces. Arab countries, despite their initially positive approach to the idea, were divided when this document was prepared. Opposition from Saudi Arabia and the Gulf states led to the project being frozen in time. These countries chose military cooperation by forming ad hoc coalitions.